A cross-sectional study to evaluate dental professionals' knowledge of antiplaque mouth rinse agents and their application in periodontal practice - Muzammil Moin Ahmed (Wolters Kluwer Medknow Publications, 2023)
Background: Mouth rinse agents reduce inflammation and microbial burden, improving periodontal clinical parameters. Yet, improper clinical use of these compounds might have several deleterious repercussions. Given the lack of research on the knowledge and application of antiplaque mouth rinse agents, this research was conducted. Methods: The research is an electronic survey wherein responses were gathered for ten items with predetermined answers in addition to covariate data. The questions were conceived to illuminate the level of knowledge possessed by dental professionals and their utilization pattern in periodontal practice. The data gathered underwent quantitative statistical analysis. Results: Participants in the study included 100 dental professionals from various disciplines, all of whom agreed that mouth rinses are a vital adjuvant in periodontal therapy. Most acknowledged being aware of the various mouth rinse agents, but their knowledge and application of mouth rinses were largely confined to chlorhexidine gluconate, with little consideration being given to alternative antiplaque agents. Conclusion: Little knowledge exists among dental professionals regarding mouth rinse agents and their appropriate application. Dental schools, clinical advisory organizations, and other establishments could educate dental professionals on the specific guidelines for utilizing antiplaque mouth rinses in a dental context, especially as an adjunct to periodontal therapy.